Genistein Protects against Spinal Cord Injury in Mice by Inhibiting Neuroinflammation via TLR4-Mediated Microglial Polarization - Xin-Wu Li; Peng Wu; Jian Yao; Kai Zhang; Gen-Yang Jin (Applied Bionics and Biomechanics)
Objective. The present study was designed to study the effect of genistein on spinal cord injury (SCI) in mice and to explore its underlying mechanisms. Methods. We established SCI mouse model, and genistein was administered for treatment. We used the Basso, Beattie, and Bresnahan (BBB) exercise rating scale to evaluate exercise recovery, and the detection of spinal cord edema was done using the wet/dry weight method. Apoptosis was determined by TUNEL staining, and inflammation was evaluated by measuring inflammatory factors by an ELISA kit. The expression of M1 and M2 macrophage markers was determined using flow cytometry, and the expression of proteins was detected using immunoblotting. Results. Genistein treatment not only improved the BBB score but also reduced spinal cord edema in SCI mice. Genistein treatment reduced apoptosis by increasing Bcl2 protein expression and decreasing Bax and caspase 3 protein expression. It also reduced the expression of inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8) in the SCI area of SCI mice. Flow cytometry analysis indicated that genistein treatment significantly decreased the ratio of M1 macrophages (CD45+/Gr-1-/CD11b+/iNOS+) and increased the ratio of M2 macrophages (CD45+/Gr-1-/CD11b+/Arginase 1+) in the SCI area of SCI mice on the 28th day after being treated with genistein. We also found that genistein treatment significantly decreased the expression of TLR4, MyD88, and TRAF6 protein in the SCI area of SCI mice on 28th day after being treated with genistein. Conclusion. Our findings suggested that genistein exerted neuroprotective action by inhibiting neuroinflammation by promoting the activation of M2 macrophages, and its underlying mechanisms might be related to the inhibition of the TLR4-mediated MyD88-dependent signaling pathway.